A 0.006mm² 1.2μW analogue-to-time converter for asynchronous bio-sensors - Leene,L; Constandinou,TG (IEEE Journal of Solid-State Circuits, 2018)
This work presents a low-power analogue-to-time converter (ATC) for integrated bio-sensors. The proposed circuit facilitates the direct conversion of electrode biopotential recordings into time-encoded digital pulses with high efficiency without prior signal amplification. This approach reduces the circuit complexity for multi-channel instrumentation systems and allows asynchronous digital control to maximise the potential powersavings during sensor inactivity. A prototype fabricated using a 65nm CMOS technology is demonstrated with measured characteristics. Experimental results show an input-referred noise figure of 3.8μ Vrms for a 11kHz signal bandwidth while dissipating 1.2μ W from a 0.5V supply and occupying 60 ×80μ m² silicon area. This compact configuration is enabled by the proposed asynchronous readout that shapes the mismatch componentsarising from the multi-bit quantiser and the use of capacitive feedback.